2021
DOI: 10.3389/frsc.2021.648551
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Characteristics and Source-Apportionment of PM2.5 During the Post-monsoon Season in Delhi, India

Abstract: In this study, we have coupled measurements, modeling, and remote sensing techniques to better delineate the source characteristics and variability of air pollutants in Delhi primarily during the post-monsoon season in 2019. We show a comparison of ambient PM2.5 (particulate matter having aerodynamic diameter ≤2.5 μm) levels and associated elements during the post-monsoon with those during a relatively clean season of monsoon (experiencing frequent wet precipitation). Air-mass back trajectories from Hybrid Sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 73 publications
3
16
0
Order By: Relevance
“…The presence of soil-based elements like Ca, K, and Mg shows their existence from natural sources such as crustal resuspension and mineral dust (Kulshrestha et al, 2003;Kulshrestha et al, 2009;Tiwari et al, 2015). Regular open-air solid waste burning, as well as diverse industrial operations, can contribute to the elevated levels of Al (Pant et al, 2016;Mehra et al, 2020;Bangar et al, 2021) as found in the present study. From soil dust, Na was recognized as a crustal element.…”
Section: Elemental Contribution To Particulate Matter In Three Locationssupporting
confidence: 67%
“…The presence of soil-based elements like Ca, K, and Mg shows their existence from natural sources such as crustal resuspension and mineral dust (Kulshrestha et al, 2003;Kulshrestha et al, 2009;Tiwari et al, 2015). Regular open-air solid waste burning, as well as diverse industrial operations, can contribute to the elevated levels of Al (Pant et al, 2016;Mehra et al, 2020;Bangar et al, 2021) as found in the present study. From soil dust, Na was recognized as a crustal element.…”
Section: Elemental Contribution To Particulate Matter In Three Locationssupporting
confidence: 67%
“…This makes air pollution significant in determining the quality of life of small children, the elderly, and patients with cardiovascular/ respiratory diseases (Arnetz et al, 2020). Although there are different sources of air pollution (Hime et al, 2018;Shi et al, 2019;Bangar et al, 2021), this study will focus on pollution from the use of caloric energy (firewood) for heating. Residential wood-burning is estimated to cause 29,000 premature deaths in Europe and North America annually (Amegah et al, 2014;Carvalho et al, 2018;Bjørner et al, 2019;Quinteros et al, 2019;Fleisch et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…PM can be emitted directly from the main sources or indirectly through the conversion of gaseous emissions in the atmosphere. Studies on the elemental composition of PM 2.5 have revealed elevated levels of elements, including Al, As, Br, Ca, Cl, Cr, Fr, K, Mg, Mn, Na, Pb, Ti, and Zn, as well as sulfate, nitrate, and ammonium ions [ 46 ]. Various sources of PM 2.5 and their chemical components have been listed ( Table 1 ).…”
Section: Sources Of Pm 25mentioning
confidence: 99%